Internal curing by superabsorbent polymers in alkali-activated slag. (September 2020) - Li, Zhenming; Wyrzykowski, Mateusz; Dong, Hua; Granja, José; Azenha, Miguel; Lura, Pietro; Ye, Guang
Abstract: In this study, internal curing by superabsorbent polymers (SAP) is utilized to mitigate self-desiccation and autogenous shrinkage of alkali-activated slag (AAS) pastes. Absorption and desorption kinetics of SAP incorporated in AAS pastes were studied with X-ray tomography. Internal curing delayed the peak of the rate of heat liberation but increased the total reaction degree of AAS pastes. Internal curing by SAP mitigated effectively the drop of internal relative humidity and the self-desiccation-induced autogenous shrinkage of AAS pastes. The cracking tendency of AAS pastes undergoing shrinkage in restrained conditions was also significantly reduced with SAP. Nonetheless, adding SAP, regardless of their content, cannot eliminate the autogenous shrinkage of AAS pastes, suggesting the existence of other autogenous shrinkage mechanism(s) besides self-desiccation.